Redox‐Switchable Calix[6]arene‐Based Isomeric Rotaxanes. Issue 47 (18th May 2018) - Zanichelli, Valeria; Bazzoni, Margherita; Arduini, Arturo; Franchi, Paola; Lucarini, Marco; Ragazzon, Giulio; Secchi, Andrea; Silvi, Serena
Abstract: Operating molecular machines are based on switchable systems whose components can be set in motion in a controllable fashion. The presence of nonsymmetrical elements is a mandatory requirement to obtain and demonstrate the unidirectionality of motion. Calixarene‐based macrocycles have proved to be very efficient hosts in the design of oriented rotaxanes and of pseudorotaxanes with strict control over the direction of complexation. A series of two‐station rotaxanes based on bipyridinium–ammonium axles was synthesized and characterized. A recently reported supramolecularly assisted strategy for the synthesis of different orientational isomers was exploited, and the ammonium unit was identified as a proper secondary station for the calixarene. Displacement of the macrocycle was triggered by electrochemical reduction of the bipyridinium primary station, and it was shown that the shuttling is influenced both by the length of the chain of the axle component and by the position of the secondary station with respect to the calixarene rims. Abstract : One‐way rotaxanes : A series of isomeric redox‐switchable calix[6]arene‐based rotaxanes were synthesized by a reagent‐less strategy. It was demonstrated that the orientation of the calix[6]arene wheel can give rise to a thermodynamic preference for shuttling among orientational isomers (see figure).